Visualisasi sistem 1nformasi jaringan distribusi listrik (Studi Kasus Kota Denpasar = A Visualisation of Information System for ElectricityDistribution Network(Case Study of Denpasar City) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
A Visualization of Information System for Electricity Distribution Network (Case Study of Denpasar City) is an SIG-based information system using spatial and non spatial data model. The system can be used inventory management for electricity distribution networks and customers. It can display information on electricity distribution network based on selected object. It is expected that this information system is able to help PLN (National Electricity Company) with planning, operational, and monitoring to period better quality and professional of services. Describing information using spatial forms (maps) and non spatial data (text) make it easy to understand since it represents facts and descriptions.